Internal Labor Markets, Firm-Specific Human Capital, and Heterogeneity Antecedents of Employee Idiosyncratic Deal Requests - Lee, Jeong-Yeon; Bachrach, Daniel G.; Rousseau, Denise M. (Organization Science, 2015)
A field study of 615 managers in 11 Korean manufacturing firms extends theory regarding labor contracting to the study of idiosyncratic deals (i-deals). Despite i-deals’ potential to benefit both employees and employers, economic theory asserts that employers attempt to reduce individual contracting by use of internal labor markets (ILMs). This study identifies limits to that assertion by identifying conditions under which i-deals are sought, despite employee participation in ILMs. Furthermore, we develop and test theory reconciling the roles of ILMs and firm-specific human capital in employee requests for i-deals. Employee reports of ILM practices are negatively related to i-deal requests, whereas firm-specific human capital is positively related to these requests. In addition, we find an interaction between the two such that the suppressive effects of ILM reports on i-deal requests hold largely for workers with low firm-specific human capital. Individuals with high firm-specific human capital tend to seek i-deals despite reported ILM practices. I-deal requests also increase with group-level heterogeneity in firm-specific human capital. In all, our findings suggest that ILMs function as economic theory asserts for workers with limited firm-specific human capital, but they are less able to reduce i-deal requests among workers with higher firm-specific human capital.